Operational effects of plyometric training in the development of explosive strength of mountain run athletes - Bakaev V.V.; Poniasov O.E.; Vasilyeva E.A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to increase the efficiency of training mountain running athletes to overcome steep climbs using plyometric training. Methods and structure of the study. The parameters of the training activity of qualified mountain running athletes aged 23.5±0.5 years were studied. The two-month training period included four two-week microcycles in which athletes performed 10 different exercises aimed at developing explosive strength in the lower extremities. Results and conclusions. A positive effect of the plyometric training method in increasing speed-strength readiness in mountain running was revealed. The mobilization stimuli of plyometric exercises, aimed at preparing for running on steeply ascending distances, determine the effectiveness of the implementation of speed-strength functionality in mountain running athletes.